A doped modified silicon monoxide-based composite negative electrode material, and a preparation method and application thereof
Patent Information
- Application Number
- CN202310174240.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Existing technologies struggle to significantly improve the conductivity and rate performance of silicon suboxide-based composite anode materials through simple and feasible methods, especially in large-scale production.
By utilizing the breaking of Si-O bonds during the disproportionation reaction of silicon suboxide, silver and a second dopant element (such as iron) are introduced for co-doping. Through mixing, drying and sintering processes, the dopant source and disproportionated Si are dispersed in the silicon suboxide matrix, thereby improving the conductivity and rate performance of the material.
This study achieves a significant improvement in the conductivity and rate performance of silicon suboxide-based composite anode materials, while also providing a simple preparation method suitable for large-scale production.
Smart Images

Figure CN116207265B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrode material technology, specifically relating to a doped and modified silicon suboxide-based composite anode material, its preparation method, and its application. Background Technology
[0002] In the field of new energy, silicon-based anode materials are the most promising high-capacity anode materials to replace graphite. However, elemental silicon is accompanied by a huge volume expansion / contraction effect (~400%) during charge and discharge. During cycling, the active material rapidly pulverizes and falls off, leading to rapid capacity decay. Silicon suboxide anode materials inherit the high capacity advantage of silicon-based anode materials (1600 mAh / g), and their unique structure allows them to generate a lithium silicate phase during the first charge and discharge cycle. This provides a buffer for the expansion of the internal nano-silicon, mitigating its volume expansion effect. Therefore, its cycle stability is significantly higher than that of pure silicon.
[0003] Although silicon suboxide (SiO2) has high specific capacity and good cycle stability, its conductivity is between that of a semiconductor and an insulator, resulting in poor rate performance. Currently, to address the poor conductivity of SiO2, most researchers have employed coating methods similar to those used for pure silicon modification, such as graphene coating, constructing conductive networks with carbon nanotubes and vapor-grown carbon fibers, titanium dioxide coating, and multilayer carbon coating. For example, CN113241426B discloses a carbon composite coated SiO2 anode material, its preparation method, and a lithium-ion battery. The method involves coating a carbon layer onto the surface of SiO2 using vapor deposition to obtain vapor-coated SiO2; mixing the vapor-coated SiO2 with pitch and boric acid, followed by carbonization and sintering, causing the pitch to carbonize and coat the surface of the vapor-coated SiO2 to form a solid-phase coated carbon layer, while simultaneously allowing boric acid to volatilize and form micropores on the material surface, resulting in a solid-phase coated SiO2 precursor; and finally, using the solid-phase coated SiO2 precursor to fabricate the anode material. CN111342032B discloses a method for preparing and applying oriented graphene-coated silicon suboxide material. The method involves placing silicon suboxide in a sealed rotary kiln and evacuating the kiln to a negative pressure state. Under heating, an organic gas is introduced into the rotary kiln, causing pyrolysis on the silicon suboxide surface. Subsequently, an auxiliary gas is introduced into the rotary kiln for etching to obtain the oriented graphene-coated silicon suboxide material. However, these methods only improve the ionic and electronic conductivity at the particle interface, without improving the intrinsic conductivity of silicon suboxide.
[0004] Besides coating methods, elemental doping modification is also a direction for improving material performance. For example, CN113526516B discloses a method for preparing modified silicon suboxide, including the following steps: (1) providing silicon raw materials and performing surface oxidation on the silicon raw materials to obtain modified silicon with a silicon oxide layer on the surface; (2) mixing the raw materials of the element to be doped with the modified silicon and performing a pre-reaction to obtain a precursor; (3) placing the precursor in a vacuum environment and heating it to carry out a doping reaction to obtain modified silicon suboxide. However, since the preparation process of silicon suboxide is a vacuum high-temperature disproportionation reaction: Si + SiO2 → SiO, it is difficult to introduce elemental doping during the preparation process, and the performance improvement is limited.
[0005] Given the above, how to design a simple and easy-to-operate doping modification method to achieve elemental doping of silicon suboxide-based composite anode materials and significantly improve the conductivity and rate performance of the materials is an urgent technical problem to be solved. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a doped and modified silicon suboxide-based composite anode material, its preparation method, and its applications. This invention utilizes the breaking of Si-O bonds during the silicon suboxide dismutation reaction to introduce doping elements, allowing the elemental dopant and dismutated Si obtained after sintering to be co-dispersed within the silicon suboxide matrix. This achieves co-doping of silver and a second doping element, effectively improving the conductivity and rate performance of the silicon suboxide-based composite anode material. Furthermore, the preparation method provided by this invention is simple, highly operable, and suitable for large-scale production.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a doped and modified silicon suboxide-based composite anode material, the method comprising:
[0009] The dopant source is mixed with a silicon suboxide-containing material and sintered to obtain the doped and modified silicon suboxide-based composite anode material;
[0010] The doping source includes a first doping source and a second doping source. The first doping source is a silver source, and the second doping source includes any one or a combination of at least two of the following: an iron source, a copper source, a zinc source, or a magnesium source.
[0011] This invention utilizes the breaking of Si-O bonds during the disproportionation reaction of silicon suboxide to introduce doping elements, so that the elemental dopant source and disproportionated Si obtained after sintering are co-dispersed in the silicon suboxide matrix, realizing the co-doping of silver and the second doping element, effectively improving the conductivity and rate performance of silicon suboxide-based composite anode materials; in addition, the preparation method provided by this invention is simple, highly operable, and suitable for large-scale production.
[0012] In this invention, disproportionated Si refers to a mixture of silicon oxide and elemental silicon generated by the disproportionation reaction of silicon suboxide.
[0013] In this invention, if only silver doping is performed, not only will the material cost be high, but the rate performance will also be significantly worse; if only the second doping source is used, the rate performance will not be ideal.
[0014] Preferably, the silver source includes elemental silver and / or silver salt.
[0015] Preferably, the silver salt includes any one or a combination of at least two of silver nitrate, silver citrate, or silver fluoride.
[0016] Preferably, the second doping source is an iron source, which includes elemental iron and / or iron salts.
[0017] Preferably, the iron salt includes any one or a combination of at least two of ferric chloride, ferric nitrate, or ferric sulfate.
[0018] Preferably, the mass ratio of the silver source to the iron source is (0.15-0.2):(0.075-0.1), wherein the silver source can be selected from 0.15-0.2, for example, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.20, etc., and the iron source can be selected from 0.075-0.1, for example, 0.075, 0.08, 0.085, 0.09, 0.095 or 0.1, etc.
[0019] In this invention, the mass ratio of silver source to iron source has a significant impact on effectively improving the conductivity and electrochemical performance of the material. If the mass ratio of silver source to iron source is too large, the material cost will increase and the performance will deteriorate; if the mass ratio of silver source to iron source is too small, excellent rate performance cannot be guaranteed.
[0020] Preferably, the silicon suboxide-containing material includes any one or a combination of at least two of silicon suboxide, carbon-coated silicon suboxide, silicon suboxide / graphite composite material, and carbon-coated silicon suboxide / graphite composite material.
[0021] Preferably, the mass ratio of the silicon suboxide-containing material to the dopant source is (8-12):(0.225-0.3), wherein the silicon suboxide-containing material is selected from the range of 8-12, for example, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5 or 12, etc., and the dopant source is selected from the range of 0.225-0.3, for example, 0.225, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29 or 0.3, etc.
[0022] In this invention, if the mass ratio of silicon suboxide-containing material to dopant source is too large, the rate performance improvement is not significant; if the mass ratio of silicon suboxide-containing material to dopant source is too small, it will result in cost waste and performance degradation.
[0023] Preferably, the specific steps of the mixing include:
[0024] (1) The first doping source and the second doping source are premixed to obtain a mixture;
[0025] (2) The mixture described in step (1) is mixed with a material containing silicon suboxide to obtain a precursor of the composite anode material.
[0026] In this invention, the premixing of the first dopant source and the second dopant source can be carried out at room temperature (23℃±2℃).
[0027] Preferably, the premixing process in step (1) is accompanied by stirring.
[0028] Preferably, during the premixing process, the stirring rate is 300-900 rpm, for example, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 70 rpm, 80 rpm or 900 rpm, etc.
[0029] Preferably, the premixing time is 8-12 minutes, for example, it can be 8 minutes, 8.5 minutes, 9 minutes, 9.5 minutes, 10 minutes, 10.5 minutes, 11 minutes, 11.5 minutes or 12 minutes.
[0030] Preferably, the mixing process in step (2) is accompanied by stirring;
[0031] Preferably, during the mixing process in step (2), the stirring rate is 300-900 rpm, for example, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 70 rpm, 80 rpm or 900 rpm, etc.
[0032] Preferably, the mixing time in step (2) is 40-80 min, for example, it can be 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min or 80 min.
[0033] Preferably, the dopant source is mixed with a silicon suboxide-containing material and then dried.
[0034] Preferably, the drying temperature is 60-100℃, for example, it can be 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃ or 100℃, etc.
[0035] Preferably, the drying time is 1-3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0036] Preferably, the drying method includes vacuum drying.
[0037] As a preferred embodiment of the present invention, the sintering atmosphere is an inert atmosphere.
[0038] Preferably, the gas in the inert atmosphere includes any one or a combination of at least two of argon, nitrogen, or helium.
[0039] Preferably, the sintering temperature is 900-1100℃, for example, it can be 900℃, 930℃, 960℃, 990℃, 1020℃, 1050℃, 1080℃ or 1100℃.
[0040] Preferably, the heating rate of the sintering is 5-15℃ / min, for example, it can be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, 11℃ / min, 12℃ / min, 13℃ / min, 14℃ / min or 15℃ / min, etc.
[0041] Preferably, the isothermal time for sintering is 4-6 hours, for example, it can be 4 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours, 5 hours, 5.2 hours, 5.4 hours, 5.6 hours, 5.8 hours or 4 hours.
[0042] Preferably, the sintering is followed by acid washing and drying to obtain the doped and modified silicon suboxide-based composite anode material.
[0043] As a preferred technical solution, the preparation method includes the following steps:
[0044] (I) Premix silver source and iron source in a mass ratio of (0.15-0.2):(0.075-0.1) at 300-900 rpm for 8-12 min to obtain a mixture;
[0045] (II) The mixture described in step (I) is mixed with a silicon suboxide-containing material at 300-900 rpm for 40-80 min, and then dried at 60-100℃ for 1-3 h to obtain a precursor of the composite anode material;
[0046] The mass ratio of the mixture to the silicon suboxide-containing material is (8-12):(0.225-0.3).
[0047] (III) The precursor of the composite anode material described in step (II) is sintered in an inert atmosphere at 900-1100℃ for 4-6 hours. After sintering, it is acid-washed and dried to obtain the doped and modified silicon suboxide-based composite anode material.
[0048] In a second aspect, the present invention provides a doped modified silicon suboxide-based composite anode material prepared by the preparation method described in the first aspect. The doped modified silicon suboxide-based composite anode material includes a silicon suboxide matrix and a first dopant source element, a second dopant source element, and disproportionated silicon dispersed in the matrix. The disproportionated silicon includes silicon and silicon oxide.
[0049] Thirdly, the present invention provides a lithium-ion battery, wherein the negative electrode of the lithium-ion battery comprises a doped and modified silicon suboxide-based composite negative electrode material as described in the second aspect.
[0050] The numerical range described in this invention includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific point values included in the range.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] (1) This invention utilizes the breaking of Si-O bonds during the disproportionation reaction of silicon suboxide to introduce doping elements, so that the elemental dopant and disproportionated Si obtained after sintering are dispersed in the silicon suboxide matrix, realizing the co-doping of silver and the second doping element, effectively improving the conductivity and rate performance of silicon suboxide-based composite anode materials.
[0053] (2) The preparation method provided by the present invention is simple, highly operable, and suitable for large-scale production. Attached Figure Description
[0054] Figure 1 This is a SEM characterization image of the doped and modified silicon suboxide-based composite anode material prepared in Example 1 of the present invention. Detailed Implementation
[0055] It should be understood that in the description of this invention, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined with "first," "second," etc., may explicitly or implicitly include one or more of that feature. In the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0056] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.
[0057] Example 1
[0058] This embodiment provides a method for preparing a doped and modified silicon suboxide-based composite anode material, the preparation method comprising the following steps:
[0059] (1) Silver nitrate and ferric nitrate with a mass ratio of 0.018:0.085 were premixed at 600 rpm for 10 min to obtain a mixture;
[0060] (2) The mixture described in step (1) is mixed with silicon suboxide at 600 rpm for 60 min and then vacuum dried at 80 °C for 2 h to obtain the precursor of the composite negative electrode material;
[0061] The mass ratio of the mixture to the silicon suboxide is 10:0.26;
[0062] (3) The precursor of the composite anode material described in step (2) is sintered in a nitrogen atmosphere at 1000°C for 5 hours. After sintering, it is acid-washed and dried to obtain the doped and modified silicon suboxide-based composite anode material.
[0063] The heating rate of the sintering temperature is 10℃ / min.
[0064] Figure 1 The SEM characterization image of the doped and modified silicon suboxide-based composite anode material prepared in this embodiment is shown. As can be seen from the figure, the surface of the composite material is non-porous and relatively rough.
[0065] Example 2
[0066] This embodiment provides a method for preparing a doped and modified silicon suboxide-based composite anode material, the preparation method comprising the following steps:
[0067] (1) Silver fluoride and ferric chloride with a mass ratio of 0.15:0.1 were premixed at 300 rpm for 12 min to obtain a mixture;
[0068] (2) The mixture described in step (1) is mixed with carbon-coated silicon suboxide at 300 rpm for 80 min, and then vacuum dried at 60 °C for 3 h to obtain the precursor of the composite negative electrode material;
[0069] The mass ratio of the mixture to the carbon-coated silicon suboxide is 8:0.3;
[0070] (3) The precursor of the composite anode material described in step (2) is sintered in an argon atmosphere at 900°C for 6 hours. After sintering, it is acid-washed and dried to obtain the doped and modified silicon suboxide-based composite anode material.
[0071] The heating rate of the sintering temperature is 5℃ / min.
[0072] Example 3
[0073] This embodiment provides a method for preparing a doped and modified silicon suboxide-based composite anode material, the preparation method comprising the following steps:
[0074] (1) Silver citrate and ferric sulfate with a mass ratio of 0.2:0.075 were premixed at 900 rpm for 8 min to obtain a mixture;
[0075] (2) The mixture described in step (1) is mixed with the silicon suboxide / graphite composite material at 900 rpm for 40 min, and then vacuum dried at 100 °C for 1 h to obtain the precursor of the composite negative electrode material;
[0076] The mass ratio of the mixture to the silica-suboxide / graphite composite material is 12:0.225.
[0077] (3) The precursor of the composite anode material described in step (2) is sintered in a helium atmosphere at 1100°C for 4 hours. After sintering, it is acid-washed and dried to obtain the doped and modified silicon suboxide-based composite anode material.
[0078] The heating rate of the sintering temperature is 15℃ / min.
[0079] Example 4
[0080] The difference between this embodiment and embodiment 1 is that the mass ratio of silver nitrate to ferric nitrate in step (1) is 0.1:0.1.
[0081] The remaining preparation methods and parameters are consistent with those in Example 1.
[0082] Example 5
[0083] The difference between this embodiment and embodiment 1 is that the mass ratio of silver nitrate to ferric nitrate in step (1) is 0.25:0.075.
[0084] The remaining preparation methods and parameters are consistent with those in Example 1.
[0085] Example 6
[0086] The difference between this embodiment and embodiment 1 is that the mass ratio of the mixture to silicon suboxide in step (2) is 7:0.3.
[0087] The remaining preparation methods and parameters are consistent with those in Example 1.
[0088] Example 7
[0089] The difference between this embodiment and embodiment 1 is that the mass ratio of the mixture to silicon suboxide in step (2) is 13:0.225.
[0090] The remaining preparation methods and parameters are consistent with those in Example 1.
[0091] Example 8
[0092] The difference between this embodiment and Embodiment 1 is that silver nitrate, ferric nitrate, and silicon dioxide are directly mixed.
[0093] The remaining preparation methods and parameters are consistent with those in Example 1.
[0094] Example 9
[0095] The difference between this embodiment and embodiment 1 is that the mixing time in step (2) is 30 minutes.
[0096] The remaining preparation methods and parameters are consistent with those in Example 1.
[0097] Example 10
[0098] The difference between this embodiment and embodiment 1 is that the mixing time in step (2) is 90 minutes.
[0099] The remaining preparation methods and parameters are consistent with those in Example 1.
[0100] Comparative Example 1
[0101] The difference between this comparative example and Example 1 is that step (1) is omitted, and the mixture in step (2) is replaced with silver nitrate.
[0102] The remaining preparation methods and parameters are consistent with those in Example 1.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 1 is that step (1) is omitted, and the mixture in step (2) is replaced with ferric nitrate.
[0105] The remaining preparation methods and parameters are consistent with those in Example 1.
[0106] Comparative Example 3
[0107] The difference between this comparative example and Example 1 is that silicon suboxide is not doped.
[0108] The remaining preparation methods and parameters are consistent with those in Example 1.
[0109] Performance testing
[0110] The negative electrode materials provided in Examples 1-10 and Comparative Examples 1-3 were combined with lithium iron phosphate to form lithium-ion batteries, and the discharge capacity of the cells at room temperature and at 0.1C / 0.33C / 1C / 2C was tested.
[0111] The test results are shown in Table 1.
[0112] Table 1
[0113]
[0114]
[0115] analyze:
[0116] A comparison of the data results from Examples 1 and 4-5 shows that the mass ratio of the first doping source to the second doping source should be controlled within the range of (0.15-0.2):(0.075-0.1). A ratio that is too large or too small will have an adverse effect on the conductivity and rate performance of the negative electrode material.
[0117] A comparison of the data results from Examples 1 and 6-7 shows that the mass ratio of the dopant source to silicon suboxide should be controlled within the range of (8-12):(0.225-0.3). A ratio that is too large or too small will have an adverse effect on the conductivity and rate performance of the anode material.
[0118] A comparison of the data results from Example 1 and Example 8 shows that the dopant source should be fully premixed before mixing with silicon suboxide; otherwise, it will have an adverse effect on the conductivity and rate performance of the anode material.
[0119] A comparison of the data results from Examples 1 and 9-10 shows that both excessively short and excessively long mixing times between the dopant source and silicon suboxide can adversely affect the conductivity and rate performance of the anode material.
[0120] A comparison of the data results from Example 1 and Comparative Examples 1-2 shows that doping with only the first doping source or only the second doping source will have an adverse effect on the conductivity and rate performance of the anode material.
[0121] A comparison of the data results from Example 1 and Comparative Example 3 shows that the absence of doping has an extremely adverse effect on the conductivity and rate performance of the negative electrode material.
[0122] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a doped and modified silicon suboxide-based composite anode material, characterized in that, The preparation method includes: (1) The first doping source and the second doping source are premixed to obtain a mixture; (2) The mixture described in step (1) is mixed with a material containing silicon suboxide to obtain a precursor of the composite anode material; The precursor of the composite anode material is sintered to obtain the doped and modified silicon suboxide-based composite anode material; the sintering temperature is 900-1100℃. The first doping source is a silver source, and the second doping source is an iron source.
2. The preparation method according to claim 1, characterized in that, The silver source includes elemental silver and / or silver salts.
3. The preparation method according to claim 2, characterized in that, The silver salt includes any one or a combination of at least two of silver nitrate, silver citrate, or silver fluoride.
4. The preparation method according to claim 1, characterized in that, The iron source includes elemental iron and / or iron salts.
5. The preparation method according to claim 4, characterized in that, The iron salt includes any one or a combination of at least two of ferric chloride, ferric nitrate, or ferric sulfate.
6. The preparation method according to claim 4, characterized in that, The mass ratio of the silver source to the iron source is (0.15-0.2):(0.075-0.1).
7. The preparation method according to claim 1, characterized in that, The silicon suboxide-containing material includes any one or a combination of at least two of silicon suboxide, carbon-coated silicon suboxide, silicon suboxide / graphite composite material, and carbon-coated silicon suboxide / graphite composite material.
8. The preparation method according to claim 1, characterized in that, The mass ratio of the silicon suboxide-containing material to the dopant source is (8-12):(0.225-0.3).
9. The preparation method according to claim 1, characterized in that, The premixing process described in step (1) is accompanied by stirring.
10. The preparation method according to claim 9, characterized in that, During the premixing process, the stirring rate is 300-900 rpm.
11. The preparation method according to claim 1, characterized in that, The premixing time is 8-12 minutes.
12. The preparation method according to claim 1, characterized in that, The mixing process described in step (2) is accompanied by stirring.
13. The preparation method according to claim 12, characterized in that, During the mixing process described in step (2), the stirring speed is 300-900 rpm.
14. The preparation method according to claim 1, characterized in that, The mixing time in step (2) is 40-80 min.
15. The preparation method according to claim 1, characterized in that, The doping source is mixed with a silicon suboxide-containing material and then dried.
16. The preparation method according to claim 15, characterized in that, The drying temperature is 60-100℃.
17. The preparation method according to claim 15, characterized in that, The drying time is 1-3 hours.
18. The preparation method according to claim 16, characterized in that, The drying method includes vacuum drying.
19. The preparation method according to claim 1, characterized in that, The sintering atmosphere is an inert atmosphere.
20. The preparation method according to claim 19, characterized in that, The gas in the inert atmosphere includes any one or a combination of at least two of argon, nitrogen, or helium.
21. The preparation method according to claim 1, characterized in that, The sintering heating rate is 5-15℃ / min.
22. The preparation method according to claim 1, characterized in that, The isothermal time for sintering is 4-6 hours.
23. The preparation method according to claim 1, characterized in that, After sintering, the material is acid-washed and dried to obtain the doped and modified silicon suboxide-based composite anode material.
24. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (I) Premix silver source and iron source in a mass ratio of (0.15-0.2):(0.075-0.1) at 300-900 rpm for 8-12 min to obtain a mixture; (II) The mixture described in step (I) is mixed with a silicon suboxide-containing material at 300-900 rpm for 40-80 min, and then dried at 60-100℃ for 1-3 h to obtain the precursor of the composite anode material; The mass ratio of the mixture to the silicon suboxide-containing material is (8-12):(0.225-0.3). (III) The precursor of the composite anode material described in step (II) is sintered in an inert atmosphere at 900-1100℃ for 4-6 hours. After sintering, it is acid-washed and dried to obtain the doped and modified silicon suboxide-based composite anode material.
25. A doped and modified silicon suboxide-based composite anode material prepared by the preparation method according to any one of claims 1-24, characterized in that, The doped and modified silicon suboxide-based composite anode material includes a silicon suboxide matrix and a first dopant source element, a second dopant source element, and disproportionated silicon dispersed in the matrix, wherein the disproportionated silicon includes silicon and silicon oxide.
26. A lithium-ion battery, characterized in that, The negative electrode of the lithium-ion battery includes the doped and modified silicon suboxide-based composite negative electrode material as described in claim 25.
Citation Information
Patent Citations
A method for preparing oriented graphene-coated silicon suboxide material and its application
CN111342032B
Carbon composite coated silicon suboxide anode material, its preparation method and lithium-ion battery
CN113241426B
A modified silicon suboxide, its preparation method and uses
CN113526516B
Composite negative electrode material and preparation method and application thereof
CN115000392A
Negative electrode material for nonaqueous electrolyte secondary battery, method of manufacturing the same, lithium ion secondary battery, and electrochemical capacitor
JP2011192453A
